Community Economy Improvement Through Digital Tourism Village in Pabean Udik Village, Indramayu - Nurfajriah Nurfajriah; Mohammad Rachman Waluyo; Santika Sari; Fajar Rahayu (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
Poverty is a complex issue encompassing multi dimensions such as economic access, social factors, culture, politics and participation in society. Specifically, rural poverty poses a significant challenge to the advancement of development in rural areas. To address the issue, based on the Indramayu Village Development Acceleration (PPDI MBKM) initiative a community service activity was conducted to improve the local economy through the restoration and the management of land or public facilities, particularly the establishments of parks as potential business ventures for the surrounding communities. The activities aimed at creating opportunities for local vendors and entrepreneurs to sell their products and services around the parks. Hopefully, the efforts open diverse business opportunities and contribute to the overall improvement of the rural economy.